2018
DOI: 10.1002/epi4.12094
|View full text |Cite
|
Sign up to set email alerts
|

The adjunctive application of transcranial direct current stimulation in the management of de novo refractory epilepsia partialis continua in adolescent‐onset POLG‐related mitochondrial disease

Abstract: SummaryFocal status epilepticus in POLG‐related mitochondrial disease is highly refractory to pharmacological agents, including general anesthesia. We report the challenges in managing a previously healthy teenager who presented with de novo epilepsia partialis continua and metabolic stroke resulting from the homozygous p.Ala467Thr POLG mutation, the most common pathogenic variant identified in the Caucasian population. We applied transcranial direct current stimulation (tDCS; 2 mA; 20 min) daily as an adjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(21 reference statements)
0
15
1
1
Order By: Relevance
“…We therefore conclude that – in this case study – tDCS did not have a beneficial treatment effect on treatment-resistant refractory epilepsia partialis continua in POLG-related mitochondrial disease. Hence, our results are inconsistent with those of Ng et al [6], who found that seizures stopped completely in a similar case study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We therefore conclude that – in this case study – tDCS did not have a beneficial treatment effect on treatment-resistant refractory epilepsia partialis continua in POLG-related mitochondrial disease. Hence, our results are inconsistent with those of Ng et al [6], who found that seizures stopped completely in a similar case study.…”
Section: Discussioncontrasting
confidence: 99%
“…A study found mitochondrial dysfunction in one third of patients with epilepsy that underwent metabolic testing [5], emphasizing that drug-resistant seizures are a frequent problem in mitochondrial disease, and that new treatments need to be developed. In a previous case report, focal seizures in a patient with POLG-related mitochondrial disease ceased after two weeks of transcranial direct current stimulation (tDCS) [6]. Since these seizures are often refractory to medical treatment and the technique is non-invasive, we tested tDCS using similar parameters as in Ng et al [6] in a patient with POLG-related mitochondrial disease and drug-resistant multifocal epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this phenomenon may be able to explain some of the unexpected long-term effects of TCS that appear in parts of the brain that were not stimulated. An example of this phenomenon is presented in [67], where seizures reoccur starting from a different brain region a month after an initially successful application of TCS.…”
Section: Node Indexmentioning
confidence: 99%
“…Epilepsia partialis continua er vanligvis behandlingsrefraktaer. Transkraniell likestrømsstimulering kan forsøkes (14), men vi har ikke kunnet bekrefte effekt. Mange forsøker ketogen diett, men det er ikke vist effektivt i denne sammenheng.…”
Section: Utredningunclassified